Negotiating Solidarity : a Social-Linguistic Approach to Job Interviews. - Lipovsky, Caroline (Cambridge Scholars Pub., 2010)
Negotiating Solidarity: A Social-Linguistic Approach to Job Interviews explores the linguistic co-construction of self-presentation in job interviews. It shows how candidates construct their professional identities, and establish co-membership and build rapport with their interviewers. Specifically, it illustrates how candidates enact their professional expertise and put their qualities forward, and highlights the linguistic features that succeed (or fail) to make a good impression on intervi ...